A NEW GENUS OF PHALANGOPSID CRICKETS FROM SOUTH AMERICA (ORTHOPTERA: GRYLLOIDEA: PHALANGOPSIDAE) - Mello, F. A. G. (REVISTA DE AGRICULTURA, 2020)
A NEW GENUS OF PHALANGOPSID CRICKETS FROM SOUTH AMERICA (ORTHOPTERA: GRYLLOIDEA: PHALANGOPSIDAE)